Effect of auricular holographic copper-plate scrapping combined with auricular acupoint pressing therapy in the treatment of nonspecific low back pain of cold-dampness obstruction type (耳部全息铜砭刮痧联合耳穴贴压治疗寒湿痹阻型非特异性腰痛效果观察) - REN Fang (任芳); ZHOU Haiying (周海英); BAI Yang (白洋); LI Lijuan (李利娟) (Association of Integrative Nursing, 2024)
Objective To investigate the effect of auricular holographic copper-plate scrapping combined with auricular acupoint pressing therapy in the treatment of nonspecific low back pain of cold-dampness obstruction type. Methods Totally 90 patients with nonspecific low back pain of cold-dampness obstruction type were randomly divided into the control group and observation group, with 45 cases in each group. All patients received routine treatment and nursing, and those in the observation received auricular holographic copper-plate scrapping combined with auricular acupoint pressing therapy for three weeks. The Numerical Rating Scale (NRS) of pain and Tradition Chinese Medicine syndrome score were compared between two groups. Results The total effective rate was 90. 48%(38/42) in the observation group, which was higher than 70. 45%(31/44) in the control group (P＜0. 01). The NRS score and Tradition Chinese Medicine syndrome score were decreased in both two groups after intervention, and NRS score and Tradition Chinese Medicine syndrome score in the observation group were lower than those in the control group(P＜0. 05). Conclusion The auricular holographic copper-plate scrapping combined with auricular acupoint pressing therapy is effective to relieve the clinical symptoms of nonspecific low back pain of cold-dampness obstruction type (目的 观察耳部全息铜砭刮痧联合耳穴贴压改善寒湿痹阻型非特异性腰痛的临床疗效。方法 选取2022年4月-2023年11月医院外科护理门诊收治的寒湿痹阻型非特异性腰痛患者90例, 按照随机数字表法分为对照组和观察组。对照组给予常规治疗和护理, 观察组在对照组基础上给予耳部全息铜砭刮痧联合耳穴贴压治疗。两组均治疗3周, 治疗结束后评估患者疼痛改善情况, 对比两组患者疼痛程度评分量表(NRS)及中医腰痛症候评分。结果 共脱落4例患者, 最终观察组纳入42例, 对照组纳入44例。观察组总有效率90. 48%(38/42), 高于对照组的70. 45%(31/44), 差异有统计学意义(P＜0. 01)。治疗后两组NRS评分及腰痛中医症候评分相比治疗前降低, 且治疗后观察组NRS评分及腰痛中医证候评分均低于对照组, 差异有统计学意义(P＜0. 05)。结论 耳部全息铜砭刮痧联合耳穴压豆能有效改善寒湿痹阻型非特异性腰痛患者的症状。)